TRANSLATION PROBLEMS OF ENGLISH IDIOMS INTO UZBEK - Nurmatova Go’zal Xakimovna; Yusupov Doniyor Hoshim o’g’li (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In this article, we have analyzed the translation of phraseology from English to Uzbek, literary texts, and the factors affecting their meaning from a linguistic point of view for the reader's understanding. In the process of translation, we classify the problems encountered in phraseologisms, proverbs and proverbs and their solutions through various examples.